Aspectos constitucionales del arbitraje. Entrevista a José Daniel Amado - Monge Morales, Gonzalo J. (Pontificia Universidad Católica del Perú, 2015)
What is the nature of arbitration? In which sourcerelies its binding force? How does its relation with the Judicial Power must be comprehended? Whichis  the  role  the Constitutional  Court  shall  havetowards it? What is the importance of arbitrationin relation with domestic and foreign investments?In the present article, the author provides answers to the aforementioned questions.  In  that  line, he mentions recent pronouncements of the Constitutional Court regarding the matter, and gives us his opinion about controversial issues that may arise.

¿Cuál es la naturaleza del arbitraje? ¿En qué fuentereside su fuerza vinculante? ¿Cómo se debe comprender su relación con el Poder Judicial? ¿Cuál esel rol que debe tener el Tribunal Constitucional frente a él? ¿Cuál es su importancia frente a las inversiones nacionales y extranjeras?En el presente artículo, el autor responde a todas las interrogantes previas. Para ello, hace alusión a recientes pronunciamientos del Tribunal Constitucional respecto de la materia, y nos brinda su opinión respecto de los aspectos controvertidos que puedan surgir.
Constitutional aspects of arbitration. Interview with José Daniel Amado
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01